Elementos de uma antropologia religiosa a partir do candomblé - Berkenbrock, Volney J. (Revista eclesiástica brasileira, 2014)
In the tradition of Western thought, the various sciences that deal with human beings - from philosophy to psychology, from theology to medicine - are heirs of a dualistic concept: matter-spirit; body-soul; physical-psychic. The thinking of yoruba-people, who arrived in Brazil by slaves, and survived, especially in religion Candomble, have a different concept of this dualistic. The human being is multidimensional and is constituted by the relationship of various dimensions. What are these dimensions and how they contribute to the composition of a concept of human being will be the object of consideration of this contribution.